2011
DOI: 10.1108/01437721111181642
|View full text |Cite
|
Sign up to set email alerts
|

Between universality and contingency

Abstract: Purpose -The purpose of this study is to examine whether the performance of the compensation system is better explained by the universalist approach or the contingent approach. The paper also attempts to determine the type of fit that yields the most promising gains in terms of perception of performance. Design/methodology/approach -Data were collected by questionnaire from 602 large organizations in three countries (Canada, France, and the UK), and from this, five hypotheses were formulated and tested using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 52 publications
(82 reference statements)
0
4
0
2
Order By: Relevance
“…On the other hand, Katou and Budhwar (2006) found that the compensation package has a significant influence on both the individual performance of employees in manufacturing industries and the organization's effectiveness and competence. Therefore, in this competitive scenario, companies are exploring compensation strategies that can lead to enhanced performance (Chênevert and Tremblay, 2011). This leads to the following hypothesis:…”
Section: Compensation and Perceived Organizational Performancementioning
confidence: 99%
“…On the other hand, Katou and Budhwar (2006) found that the compensation package has a significant influence on both the individual performance of employees in manufacturing industries and the organization's effectiveness and competence. Therefore, in this competitive scenario, companies are exploring compensation strategies that can lead to enhanced performance (Chênevert and Tremblay, 2011). This leads to the following hypothesis:…”
Section: Compensation and Perceived Organizational Performancementioning
confidence: 99%
“…Measuring the effectiveness of reward management based on perceptions rather than on objective measures is the method of choice in this study, as we examined the influence of in-group favoritism, a phenomenon which is driven solely by perceptions and subjective opinions, on the centralization considerations of reward managers. Furthermore, this assessment is applicable to various sectors and countries, while objective effectiveness is not due to the variety of influencing factors in different environments (Chênevert & Tremblay, 2011). However, we have to admit that the small sample size did not allow for a systematic inclusion of many control variables and that larger sample sizes could have led to more explanatory power for the data and, therefore, more significant results.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived effectiveness of reward management was measured according to Chênevert and Tremblay (2011), albeit with one modification: The term “pay” was exchanged for the term “reward,” since this term is broader and captures benefits and relational returns as well; for example, “ Our reward policies appear to enjoy widespread acceptability among employees .” The response format included a 5-point Likert scale (1 = agree strongly ; 5 = disagree strongly ), and effectiveness scores ranging from 1 to 5 were reversed (5 = maximum perceived effectiveness ; 1 = minimum perceived effectiveness ). This variable was also assessed separately with respect to the three management levels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hal ini dimaksudkan bahwa sistem pembayaran dan pemberian kompensasi harus sesuai dengan peraturan dan penetapan dari perusahaan dengan seistem penilaian kinerja karyawan untuk menciptakan keadilan dalam pemberian kompensasi pada seluruh karyawannya. Untuk kinerja optimal, sistem kompensasi harus terdiri dari kebijakan yang konsisten baik antara karyawan individu atau sendiri dan dengan kebijakan HRM lainnya (Denis Chênevert, 2011).…”
Section: Analisis Model Struktural (Inner Model) Persamaan Strukturalunclassified